Minimum-Area ellipse containing a finite set of points. II - Petunin, Yu. I.; Rublev, В. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We continue the investigation of the problem of construction of a minimum-area ellipse for a given convex polygon (this problem is solved for a rectangle and a trapezoid). For an arbitrary polygon, we prove that, in the case where the boundary of the minimum-area ellipse has exactly four or five common points with the polygon, this ellipse is the minimum-area ellipse for the quadrangles and pentagons formed by these common points.